Sustaining ocean fisheries poses challenge for resource managers - C Dewees (California Agriculture, 1997)
California is one of the world's most productive and intensely harvested marine fisheries areas. Increased fishing, habitat degradation, expanding human population and decreases in water quality and quantity have put great stress on the state's coastal marine resources. Research and extension activities funded by California Sea Grant, DANR and the California Resources Agency focus on improving the methods and policies needed to manage fisheries. Significant changes in the way we manage these resources are likely to occur in the 21st century.